Asas Pembuktian Terbalik Tindak Pidana Pencucian Uang dalam Globalisasi Hukum - Muhammad Nurul Huda (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
In Indonesia , the burden of proof principle was first introduced in the Act of corruption , and in 2010 was introduced in the Act money laundering . The principle of reverse burden of proof in Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering is not recognized in Law No. 25 of 2003 on Money Laundering preexisting . The principle of reversed burden of proof is the influence of the globalization of law . This is evident from the rules of the UNCAC , each participating country is required to make adjustments to the existing rules in the UNCAC . In the UNCAC rule that to accelerate in the fight against corruption and money laundering , each participating country are advised to incorporate the principle of proof is reversed. It is useful in addition to tracking the money proceeds of crime as well as to give an opportunity to the accused to prove that their wealth is not derived from a criminal offense